2019
DOI: 10.17494/ogusbd.548346
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmen Adaylarının Fen Laboratuvarında Argümantasyon Tabanlı Öğretime Yönelik Görüşlerinin İncelenmesi

Abstract: Bu çalışma kapsamında, Argümantasyon Tabanlı Öğretim (ATÖ) yönteminin fen bilimleri laboratuvar uygulamalarında kullanılabilen etkili bir öğretim yöntemi olduğu durumu sınıf öğretmen adaylarının görüşleri ve hazırbulunuşluk durumları incelenerek ortaya koyulmuştur. Nitel araştırma yöntemlerinden durum çalışması kullanılarak yürütülen bu çalışmada toplamda 28 sınıf öğretmen adayı ile sekiz haftalık ATÖ uygulaması yapılmıştır. Uygulamanın ilk ve son haftalarında öğretmen adaylarının görüşlerinde ve hazırbulunuşl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
3
0
1
Order By: Relevance
“…Besides, the students claimed that the desire to defend an idea and refute the counter-idea in academic writings provides motivation for doing more research. These thoughts coincide with the data in the literature that argumentation arouses a sense of curiosity, develops researchinquiry skills, directs the individual to research and motivates him/her (Apaydın and Kandemir, 2018;Özcan et al, 2018;Karaer et al, 2019). Within the scope of the present research, some students stated that argumentation contributed to the development of critical thinking skills.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…Besides, the students claimed that the desire to defend an idea and refute the counter-idea in academic writings provides motivation for doing more research. These thoughts coincide with the data in the literature that argumentation arouses a sense of curiosity, develops researchinquiry skills, directs the individual to research and motivates him/her (Apaydın and Kandemir, 2018;Özcan et al, 2018;Karaer et al, 2019). Within the scope of the present research, some students stated that argumentation contributed to the development of critical thinking skills.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…When the main problem situations encountered by teachers are examined, it is revealed that they have difficulty in writing questions/giving feedback suitable for argumentation (Huang, Wang, Huang, Chen, Chen & Chang, 2011;Prusak, Hershkowitz & Schwarz, 2012;Schwarz Schur, Pensso & Tayer, 2011); they have difficulty in evaluating the quality of their arguments (Aktamış & Hiğde 2015;McNeill, Gonzalez Howard, Katsh Singer & Loper, 2016;Namdar & Salih, 2017;Öztürk, 2017); that they may need support in time management (Aktamış & Atmaca, 2016;Karaer, Karademir & Tezel, 2019;Namdar & Demir, 2016;Namdar & Tuskan, 2018) and that they find the in-service training on argumentation inadequate (Kayaduman, Sırakaya & Seferoğlu, 2011;Namdar & Tuskan, 2018;Türel, 2012) was understood. In this context, it is important to create instructional designs for teachers to effectively apply argumentation in the classroom.…”
Section: Findings Findings Derived From the Literature Reviewmentioning
confidence: 99%
“…Argümantasyonun fen eğitimindeki önemi ve etkisi bilinmesine rağmen sınıflarda yeterince bu sürecin uygulanmadığı bilinmektedir (Driver ve diğerleri, 2000; Hiğde ve Özcan, 2015). Argümantasyonun farklı değişkenler açısından incelendiği birçok çalışma mevcut olup argümantasyon düzeyini belirlemeye yönelik yapılan çalışmalar üniversite öğrencileri (Demirci 2008;Karaer, Karademir ve Tezel, 2019;Yeşiloğlu, 2007); fen öğretmenleri (Özcan, Aktamış ve Hiğde, 2018;Yıldırır ve Nakipoğlu, 2014) ve lise öğrencileri (Çetin ve diğerleri, 2014;Yalçın Çelik ve Kılıç, 2017) ile sınırlıdır. İlköğretim öğrencilerin feni öğrenebilmeleri için kanıt-iddia-gerekçe kullanarak bilgiyi yapılandırmaları, araştırma ile uğraşarak argümanlar oluşturmaları gerekmektedir (McNeill, 2011).…”
Section: Problem Durumuunclassified